Evaluation of correlation between intrafractional residual setup errors and accumulation of delivered dose distributions in single isocenter volumetric modulated arc therapy for multiple brain metastases. (June 2022) - Tsuruta, Yusuke; Nakamura, Mitsuhiro; Nakata, Manabu; Hirashima, Hideaki; Zhou, Dejun; Uto, Megumi; Takehana, Keiichi; Fujimoto, Takahiro; Mizowaki, Takashi
Highlights: Accurate dose distribution is important for patient outcomes. Intrafractional residual setup errors (RSEs) can affect dose distribution. RSEs can lead to potential displacement of gross tumor volume (GTV) position. Intrafractional RSEs in this study were low. GTV D99.5% and D0.5% were not affected by distance of the GTV from the isocenter. Abstract: Purpose: To evaluate the displacement of gross tumor volume (GTV) positions caused by intrafractional residual setup errors (RSEs) and to accumulate delivered dose distributions considering intrafraction RSEs in fractionated-stereotactic radiotherapy (f-SRT) with single isocenter volumetric modulated arc therapy (SI-VMAT) for multiple brain metastases. Methods: Overall, 72 consecutive patients who underwent f-SRT with SI-VMAT for multiple brain metastases were included. For all patients, 6D correction was performed using the ExacTrac X-ray (ETX) system. GTV displacement ( ΔD ) was calculated considering the intrafractional RSEs measured by the ETX system during irradiation. The correlation between ΔD and the distance from the isocenter to each GTV ( d ) was analyzed. Computed tomography (CT) images considering the intrafractional RSEs were generated for five patients with ΔD  > 1 mm. The delivered dose distributions for all fractions were reconstructed on the corresponding CT, followed by their accumulation. Results: The 95th percentile of ΔD from 7, 270 resultant center positions of 417 GTVs was 0.92 mm. No correlation was observed between ΔD and d . For 53 GTVs from five patients with ΔD  > 1 mm, the difference of GTV D99.5% and D0.5% between the planned and accumulated values was −0.4 ± 2.5% and −1.0 ± 0.8%, respectively. There was no correlation between d and the difference of GTV D99.5% and D0.5% . Conclusions: We found no significant difference in GTV D99.5% and D0.5%, despite the location of GTVs far from the isocenter. However, it should be noted that this result was because the intrafractional RSEs were reduced to a clinically acceptable level.